2018
DOI: 10.9741/2578-2118.1010
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analytic Procedures for Career and Technical Education Post-secondary Researchers and Practitioners

Abstract: Meta-analytic studies are syntheses of literature in which researchers use statistical means to summarize the findings presented across primary studies. They are of great interest in the fields of medicine and social sciences with numerous examples published in peer-reviewed journals. However, it appears that career and technical education (CTE) researchers are either not performing these research syntheses, or are not publishing their findings. Thus, there are three purposes to this manuscript. The first is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The mean effect size of reading comprehension on participants' mathematics skills was r = .50, with a 95 percent confidence interval varying between .47 and .52. This statistically significant value revealed that reading comprehension had a large effect size on mathematics skills of K-12 students based on Cohen's ( 2007) criteria (Oh-Young et al, 2018).…”
Section: General Characteristics Of Research Datamentioning
confidence: 82%
“…The mean effect size of reading comprehension on participants' mathematics skills was r = .50, with a 95 percent confidence interval varying between .47 and .52. This statistically significant value revealed that reading comprehension had a large effect size on mathematics skills of K-12 students based on Cohen's ( 2007) criteria (Oh-Young et al, 2018).…”
Section: General Characteristics Of Research Datamentioning
confidence: 82%
“…We systematically employed document analysis guided by the objectives to identify emergent themes that allowed for development of a framework for the topic. Borenstein et al (2009) defined a systematic review as the process of synthesizing results by constructing a thematic story to fit the literature base (Oh-Young et al, 2018). Following recommendations of Borenstein et al (2009), our systematic review included listing the search criteria, explaining methodologies for how the studies were evaluated and analyzed, and describing the characteristics of the studies in a summary table.…”
Section: Review Approach/ Frameworkmentioning
confidence: 99%
“…We described our search criteria, methods of analysis, and provided direct quotations from the articles to establish dependability. The lead researcher oversaw the entire process as an additional measure to ensure consistency in coding (Oh-Young et al, 2018).…”
Section: Analysis Techniques and Trustworthiness Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson correlation coefficient (r = ES) was calculated as the effect size of each independent study. In the interpretation of the effect sizes, value ranges offered by Cohen (1992) and Rosenthal (1996) were used (Oh-Young, Gordon, Xing & Filler, 2018). Table 2 provides ES = r interpretation value ranges.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%